A "turn-on" Cr3+ ion probe based on non-luminescent metal–organic framework-new strategy to prepare a recovery probe. Issue 23 (1st June 2021) - Zhang, Pei-Pei; Song, Bo; Li, Zhongyi; Zhang, Jian-Jun; Ni, Ai-Yun; Chen, Jun; Ni, Jun; Liu, Shuqin; Duan, Chunying
Abstract : Present here is a MOF probe, which exhibits a remarkable luminescence recovery for the selective detection of Cr 3+ ion with a detection limit of 7.52 × 10 −8 M, as well as a new pre-quench strategy and recognition mechanism for MOF-based probes. Abstract : Highly selective and sensitive, and low detection limit probes that can work in aqueous solutions are of great significance for detection. Presented here is a unique metal–organic framework of [Eu2 L3 (DMF)3 ]·2DMF·5H2 O (1 ) that shows a luminescence recovery for the selective detection of Cr 3+ ions in an aqueous solution with a calculated detection limit as low as 7.52 × 10 −8 M. Both single-crystal to single-crystal characterization and Hirschfeld surface analysis revealed that 1 is pre-quenched due to self-absorption caused by the aggregation of aromatic groups between ligands. Only the binding of Cr 3+ ions reduces the aggregation degree of ligand aromatic groups, which leads to a reduction in the self-absorption effect and ultimately causes the probe to show a turn-on response to Cr 3+ ion. Furthermore, the probe can potentially find practical applications due to its recyclability, stability in aqueous solutions and convenience to prepare test strips for visual detection. This work not only develops a new strategy for the fabrication of pre-quenched MOF-based probes but also provides a new sensing mechanism. Thus, it gives a new insight into the development of MOF-based probes with excellent recovery response.